2013
DOI: 10.1111/scd.12048
|View full text |Cite
|
Sign up to set email alerts
|

Oral health champions in long‐term care facilities—a pilot study

Abstract: This preintervention/postintervention pilot study examined impact of onsite support by a dental hygiene champion (DHC) on oral health and quality of life (QOL) of elderly residents in three long-term care facilities (LTCFs) in Arkansas. Oral health and oral health-related QOL were operationalized using the Oral Health Assessment Tool (OHAT) and Geriatric Oral Health Assessment Index (GOHAI), respectively. CNAs in Facility A received standardized oral health education/materials with onsite DHC support. Facility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 35 publications
4
33
0
Order By: Relevance
“…Even with the clear need for future research into these issues, actions can be implemented now based upon the findings from these two questionnaire surveys and the large number of oral health status surveys of disabled individuals in the United States . Given the access difficulties to oral health care that many PM&R in‐patients face upon discharge from their PM&R hospitalization, the quality of their lives can be improved if during their multimonth PM&R hospitalization their own backlog of needed dental care can be attended to during their PM&R hospitalization as a fully integrated PM&R service along with the existing array of PM&R services provided for them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with the clear need for future research into these issues, actions can be implemented now based upon the findings from these two questionnaire surveys and the large number of oral health status surveys of disabled individuals in the United States . Given the access difficulties to oral health care that many PM&R in‐patients face upon discharge from their PM&R hospitalization, the quality of their lives can be improved if during their multimonth PM&R hospitalization their own backlog of needed dental care can be attended to during their PM&R hospitalization as a fully integrated PM&R service along with the existing array of PM&R services provided for them.…”
Section: Discussionmentioning
confidence: 99%
“…The dual purposes of this project were: (1) to discern the current expert medical opinion and practices in 2014 regarding the provision of oral health services available to the Physical Medicine & Rehabilitation (PM&R) patients, during their stay in PM&R units of hospitals, and as well as after their discharge; and, (2) to compare these current findings with the findings from a survey conducted 40 years prior in 1974 using the same survey questionnaire. While there is an identifiable literature on the oral health status of handicapped and/or disabled adults living either in institutions or at‐large in the community in the United States, all articles report that the oral health status for these adults ranges from bad to horrid, with a notable lack of access to dental care. As based upon a current full‐literature search by a university‐based biomedical librarian, only a single published article exists on the specific topic of oral health services in PM&R programs and that was the article that presented the findings from our group's 1974 survey .…”
Section: Introductionmentioning
confidence: 99%
“…Educational sessions by dental hygienists to nursing staff as well as short‐term professional oral care from dental hygienists once a week have shown only limited effects . A pilot study suggested that on‐site dental hygienist support in long‐term care facilities may positively impact the oral health of residents requiring assistance with their oral care and that further research in such a concept is required …”
Section: Clinical Relevancementioning
confidence: 99%
“…A number of studies suggest that the personal attitudes and values of PCAs related to oral hygiene remain one of the most significant barriers to residents receiving adequate oral health assistance . Barriers to providing daily oral care reported by PCAs include the lack of time, a perceived lack of support by facility management, lack of knowledge or training for care staff , residents refusal or psychological barriers to perform oral hygiene care in a resident's mouth .…”
Section: Introductionmentioning
confidence: 99%